Web-Based Sales Force Automation Implementation Using Extreme Programming at CV. Samudra Jaya - Siti Farikha Jauhari Rahmadhani; Dwi Fatrianto Suyatno (Universitas Negeri Surabaya, 2026)
The sales process at CV. Samudra Jaya is currently conducted conventionally, relying on manual order recording and daily visit reports. This condition results in a high risk of human error, slow information flow between divisions, and difficulties for management in effectively monitoring salesman performance. This study aims to develop a web-based Sales Force Automation (SFA) system to digitize and automate the company's sales business processes. The system development approach applied is Extreme Programming (XP), encompassing planning, design, coding, and testing phases, selected for its flexibility in adapting to changing client needs. The application is built using the Laravel framework and MySQL database. The result of this research is an integrated SFA system that covers customer data management, salesman territory tracking, sales transaction recording, monthly target management, and automated financial reporting. System testing using the Black Box method demonstrates that all functions operate validly and meet operational requirements. The implementation of this SFA system successfully enhances sales administration efficiency, increases salesman performance transparency, and provides accurate real-time data to support strategic decision-making by management.